Archaeological Heritage Legislation and Indigenous Rights in Latin America: Trends and Challenges - Endere, Maria Luz (2014)
The recognition of the rights of indigenous peoples has been on the political agenda in Latin America since the 1980s, although it has not always been reflected in the legal systems of the countries in the region. Most of them have passed laws that grant legal recognition to indigenous communities and have recognized their rights in the national constitutions. However, these rules do not always refer to some particular aspects of the indigenous culture, such as those related to their cultural heritage. In general, the archaeological remains are ruled by specific laws that do not consider, or vaguely mention, the indigenous peoples’ rights and their participation in the decision-making process. As a result of the lack of consistency between the indigenous and cultural heritage laws in most countries, the participation of indigenous peoples in heritage management is still exceptional.